2018
DOI: 10.1002/cam4.1820
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase A: A key player in carcinogenesis and potential target in cancer therapy

Abstract: Elevated glycolysis remains a universal and primary character of cancer metabolism, which deeply depends on dysregulated metabolic enzymes. Lactate dehydrogenase A (LDHA) facilitates glycolytic process by converting pyruvate to lactate. Numerous researches demonstrate LDHA has an aberrantly high expression in multiple cancers, which is associated with malignant progression. In this review, we summarized LDHA function in cancer research. First, we gave an introduction of structure, location, and basic function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
332
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(380 citation statements)
references
References 127 publications
11
332
0
5
Order By: Relevance
“…As examples, upregulation of LDHA levels in pancreatic and esophageal cancer have been associated with metastasis, tumor stage, tumor recurrence, and patient survival (137). However, LDHA expression in malignant tumor tissues does not correlate consistently with serum LDH levels, which may indicate that these are independent prognostic factors in cancer (138,139). Studies on lactate transporters (MCTs/CD147) are not as solid as for LDH, but also reveal prognostic value ( Table 1) (41).…”
Section: Lactate Metabolism As a Prognostic And Therapeutic Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…As examples, upregulation of LDHA levels in pancreatic and esophageal cancer have been associated with metastasis, tumor stage, tumor recurrence, and patient survival (137). However, LDHA expression in malignant tumor tissues does not correlate consistently with serum LDH levels, which may indicate that these are independent prognostic factors in cancer (138,139). Studies on lactate transporters (MCTs/CD147) are not as solid as for LDH, but also reveal prognostic value ( Table 1) (41).…”
Section: Lactate Metabolism As a Prognostic And Therapeutic Toolmentioning
confidence: 99%
“…LDHA overexpression has been associated with increased cancer aggressiveness and targeting has been tackled both genetically and pharmacologically. There are different types of LDHA inhibitors, including the pyruvate-competitive (e.g., oxamate), the NADH-competitive (e.g., gossypol), the pyruvate and NADH-competitive (N-hydroxyindoles), and the free enzymebinding inhibitors (galloflavin) (138). LDH pharmacological inhibition reduces lactate production, impairs cell proliferation in vitro, and reduces tumor size in vivo, either with LDH inhibitors alone or in combination with other agents (138,141).…”
Section: Lactate Metabolism As a Prognostic And Therapeutic Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammad et al [139] showed that increased expression of LDHA and PKM2 in pancreatic biopsy specimens from patients correlates with poor survival. Studies investigating the LDH expression levels in tumor and serum found that high tissue expression is not entirely consistent with elevated serum levels, indicating that tumor LDHA expression and serum levels are two independent predictors of the disease [140]. In our analysis, LDHA was identified in six secretome studies and only two from the proteome, suggesting that this enzyme may be secreted to perform its functions in tissues distant from the primary tumor focus, exacerbating the tumor progression.…”
Section: Discussionmentioning
confidence: 70%
“…Specific metabolites are of great biochemical significance. For an example, a high level of lactate in blood can be a sign of liver and kidney diseases even the cancer, therefore the quantification of functional metabolites shows great potential application in disease diagnosis and pathogenesis 19,20 . In our protocol, we used a set of external standards each containing at least five-levels concentration to establish the calibration curves, finally, 84 key metabolites can be absolutely quantitated by the established LC-MS method ( Table 2).…”
Section: Resultsmentioning
confidence: 99%